2016
DOI: 10.1007/s00420-016-1169-8
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to silicon carbide and cancer risk: a systematic review

Abstract: The increased risk of lung cancer detected in the SiC production industry appears to be associated with high exposure levels to total dust, including crystalline silica and cristobalite which occurred in this industry in the past decades. It may not persist under current exposure circumstances, characterized by lower levels and use of personal protection equipment. Commercial users of SiC-based products were not affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Crystalline silica is a known carcinogen for bronchopulmonary cancers and also an environmental factor involved in the development of SSc (120). Many other environmental components have been suspected or confirmed as playing a role in the emergence of SSc, such as organic solvents, pollutants, welding fumes, pesticides, etc (121124).…”
Section: Shared Mechanisms In Cancer and Systemic Sclerosismentioning
confidence: 99%
“…Crystalline silica is a known carcinogen for bronchopulmonary cancers and also an environmental factor involved in the development of SSc (120). Many other environmental components have been suspected or confirmed as playing a role in the emergence of SSc, such as organic solvents, pollutants, welding fumes, pesticides, etc (121124).…”
Section: Shared Mechanisms In Cancer and Systemic Sclerosismentioning
confidence: 99%
“…One study reported increased respiratory cancer rates in a metal fabrication facility [ 75 ]; however, those cases also included mesothelioma and laryngeal cancer. A systematic review found an increased lung cancer risk in silicon carbide workers [ 76 ]. As these workers were also exposed to silica dust, no clear attribution to hard metals could be concluded.…”
Section: Resultsmentioning
confidence: 99%
“…B offetta et al . [ 93 ] reported an increased risk of lung cancer with elevated crystalline silica concentrations, especially cristobalite exposure in silicon carbide production workers. Though silicosis is predominantly seen in construction and stone workers, miners and coal workers involved in mining operations like sandblasting, surface drilling and roof bolting are exposed to high levels of RCS dust clouds for extended periods.…”
Section: Occupational Dust-associated Lung Diseasesmentioning
confidence: 99%